Food Advertising Literacy Training Reduces the Importance of Taste in Children’s Food Decision-Making: A Pilot Study - Ha, Oh-Ryeong; Killian, Haley; Bruce, Jared M.; Lim, Seung-Lark; Bruce, Amanda S. (Frontiers in Psychology, 2018)
Television food advertising influences children’s food choices. The attribute of “taste” drives children’s food choices, and exposure to food commercials can increase the importance of “taste” when children make food decisions. The current pilot study explored whether food advertising literacy training influences children’s food choices. In particular, whether the training would change the way children weigh the importance of taste attributes in their food decisions. Thirty-nine children ages 8-13 were recruited. Twenty-three of those children had four sessions of food advertising literacy training (one week): children watched four videos of food commercials embedded with factual narratives (i.e., building cognitive defenses; e.g., “commercials want to sell products”) and evaluative narratives (i.e., changing affective responses toward commercials; e.g., “these foods don’t make you happy”). The first and last sessions were held in the laboratory, and the second and third sessions were at home. During the training, children were encouraged to think aloud while watching commercials and provided narratives to encourage active information processing. At baseline and post-training, children made binary eating choices for 60 foods, and rated each food item on health and taste. We fitted linear regression models to examine whether taste and health attributes predicted unique variance in each child’s food choices. The results showed that taste attributes in children’s food choices was significantly decreased after completing the training. This finding suggested that improving food advertising literacy could be helpful for reducing the influence of taste attributes in the food decision-making process. Also, the cognitive literacy training increased children’s critical thoughts toward commercials during thinking aloud. These findings suggest that food advertising literacy training was helpful for reducing the importance of “taste” in children’s food decisions. In contrast, sixteen children in the control condition (i.e., watching four videos of food commercials without narratives in one week) did not show any significant change in their food choices. Future research should investigate the utility of food advertising literacy training for the promotion of healthy eating and the prevention of childhood obesity.